Towards sustainable continuous production of azo dyes: possibilities and techno-economic analysis - Shukla, Chinmay A.; Kute, Mahesh S.; Kulkarni, Amol A. (Green Chemistry, 2021)
A novel continuous process for synthesizing azo dyes using a bubble column reactor is reported. Continuous experiments were successfully performed for Sudan-I dye and Solvent Yellow 16 dye with a yield [and productivity] of 92.04 +/- 3.50% [1.68 +/- 0.13 kg day(-1)] and 96.60 +/- 2.18% [1.92 +/- 0.04 kg day(-1)], respectively. Experiments were performed at a higher slurry concentration similar to 5% (w/w) without any clogging. The results were extended for performing a detailed techno-economic analysis for 5 TPD Sudan-I azo dye production as a case study. The results indicate that the cost of the continuous process is almost 4.68 times lower than that of the corresponding batch process. Furthermore, the footprint for a continuous plant can be lowered by 2.4 to 4.5 times when compared to the batch process depending on different refilling strategies for feed storage tanks. A continuous process may require 39-42% less water than the industrial batch process.